Strategies for achieving the sustainable development goals across the wine chain: a review - Brito, Cátia; Pereira, Sandra; Martins, Sandra; Monteiro, Ana; Moutinho-Pereira, José Manuel; Dinis, Lia (Frontiers in Sustainable Food Systems, 2024)
In the face of escalating climate change impacts, the Sustainable Development Goals (SDGs) set forth by the United Nations present a comprehensive blueprint for achieving a better and more sustainable future for all. The wine industry, with its extensive global reach and significant economic impact, holds a unique position to contribute toward these goals. This review examines how the wine industry can, directly and indirectly, support all 17 SDGs through a multidisciplinary approach, incorporating extensive literature analysis. The study explores the alignment of wine industry practices with the SDGs across three key pillars: social, environmental, and governance goals. Social initiatives focus on enhancing livelihoods, food security, fair and safe working conditions, inclusive and ethical development among the workers and communities, education, and economic growth. Environmental efforts emphasize reducing the industry’s carbon footprint, conserving water, improving water and energy use efficiency, improving grapevine resilience against adverse environmental conditions, minimizing pollution, protecting biodiversity, creating more sustainable cities, and promoting moderate wine consumption. Governance goals highlight the importance of regulatory frameworks, wine industry standards, and stakeholder engagement in promoting sustainable, responsible and ethical practices, contributing to effective partnerships and institutional capacity. Conclusions highlight the wine industry’s commitment to sustainability as a catalyst for positive change, demonstrating that profitability and environmental stewardship can coexist. Future perspectives call for enhanced collaboration, research, education, supportive policies, robust monitoring, and equality initiatives. By embracing sustainable practices, the wine industry can play a vital role in advancing the global agenda for a more equitable, resilient, and sustainable future.